Role of Socioeconomic Factors to overcome Micronutrient Malnutrition in Pakistan: Application of Partial Proportional Odds Model - Amjad, Muhammad; Akbar, Muhammad (Progress in Nutrition, 2020)
The study determines the role of some important socioeconomic factors to overcome micronutrient malnutrition at household level in Pakistan using cross sectional data taken from national survey HIECS 2015-16. Sample data shows that availability of five out of eleven micronutrients is less than the requirements of more than 70% households which reveals the worst situation of micronutrient malnutrition in Pakistan. The study concludes that household’s income, maternal paid employment, agricultural employment, Benazir Income Support Program (BISP) and rural residential status are the important factors for improving micronutrient malnutrition in Pakistan. Varying estimates of income across the two cut-points induce that significant rise of overall households’ income level on the basis of sustainable economic growth will be effective to overcome hidden hunger in Pakistan. Live stock ownership and cultivation of agricultural land seem to have the most effective role for improving micronutrient security. The most critical result is insignificance of educational dummies which implies that even educated parents are not aware of the importance of micronutrients. Adverse impact of paternal paid employment induces revision of salary structure and minimum wage level along with annual increase according to the prevailing rate of inflation in the economy. U type quadratic impacts of household size as well as head age, and the adverse impact of dependency ratio induce effective policies to control high birth rate in Pakistan. It may be concluded that sufficient financial resources by raising households’ income level, growth of agricultural sector, women financial empowerment, effective family planning and continuation of BISP are the important recommended policy guidelines but creation of awareness about nutrition and balanced diet for a healthy family is the most important to overcome hidden hunger in Pakistan.